Avaliação do tratamento e da destinação do lodo de esgoto da estação de tratamento de esgoto do município de Francisco Beltrão/PR - Feron, Gabriela (2018)
All Sewage Treatment Station (STS) generate sewage sludge during treatment process, considered at first a waste. This work had the general objective of investigating and evaluating the procedures for treatment, disposal, use and monitoring of the sewage sludge produced in the STS-Marrecas, of the municipality of Francisco Beltrão, through interviews with Sanepar professionals and with the farmers who received the biosolids. This research was developed using some methodological procedures, the first one concerns a theoretical discussion about basic sanitation, sewage and sludge treatment from this process and ways of using sewage sludge. Then, the collection and analysis of the Federal and State legislation regarding the collection and treatment of the sewage, as well as the production of the biosolid and its use was made. In addition to this secondary information obtained from other works and legal norms, the research used primary data obtained through interviews with subjects involved in the treatment and disposal of sewage sludge in the municipality of Francisco Beltrão. Therefore, the actions carried out regarding the management, treatment and disposal of sewage sludge were collected from Sanepar by means of a script of open questions (Appendix A). Another source of data is the reports of the analyzes of the sludge produced at the station and the soils that receive the material. To know the history of the destination of the sludge in Paraná, contacts were made with engineers responsible for this action in the Southwest and other regions of Paraná. Interviews were conducted with the farmers who received the sewage sludge from the STS-Marrecas to use it for agricultural purposes (Appendix B). The sewage produced in the municipality of Francisco Beltrão receives a complete treatment, going through four phases, being considered, then, a STS of tertiary treatment. The sludge produced in STS-Marrecas is allocated for agriculture. The distribution is carried out annually and the receiving areas of biosolids are previously analyzed to ascertain the need of sludge application. After the application there is also a monitoring by the sanitation company. All the analyzes performed in the sewage sludge show favorable results for use in agriculture. All farmers stated that they perceived improvements in their plantations after the use of biosolids as fertilizers and although they are not aware of the legislation, they have some information about the restriction of the use of sludge. It is noteworthy that although good work is being done on the distribution and orientation of sludge use, some analyzes have not been carried out. In order to have a totally safe use, it is essential that all analyzes be done, both sludge and agricultural soils ones.